How is a best friend? Friendship’s characteristics in Argentine children - Greco, Carolina (Actualidades en Psicología, 2019)
The aims were to inquire the concept of best friend in school children and to explore the best friend concept as a protective factor against situations of mistreatment between peers. A qualitative methodology was chosen and focus groups made. The sample was made up of 85 schoolchildren, from 4th to 7th grade (M = 10.68, SD = 1.34). The analysis was carried out via constant comparative method. The emergent categories were: companionship, conflicts, fraternity, fidelity, trust, help, positive emotions and moral aspects, manifestations of violence and search for dialogue with the aggressor, affective containment towards the victim and recourse for teacher support. Different conceptualizations are interpreted considering cognitive and socioemotional development. Friendship is a psychosocial resource to cushion the effects of rejection and foster socioemotional development.